Sudden Cardiac Death in Athletes - Khan, Khyber (Trinity Student Medical Journal, 2007)
With the death of several well known athletes in the last thirty years, sudden cardiac death (SCD) has become of interest among many physicians. A series of studies conducted by American cardiologist and researcher, Dr. Barry J. Maron, have identified the major aetiologies in young athletes. In Ireland, Dr. Fionnuala Quigley, GP and lecturer in sports medicine, conducted a study that identified the main causes of SCD occurring in sport from 1987 to 1997. This data emphasized the causees of SCD in athletes over 35. This paper gives an overview of the main conditions that can lead to SCD in athletes, and discusses the methods and challenges of implementing a screening program.